Distance and Within-Country Diversity Effects on Foreign Acquisitions - DOW, Douglas (Institutional Knowledge at Singapore Management University, 2014)
This paper explores how within-country diversity, both in terms of language and religion, influences the ownership structure of foreign acquisitions. Numerous commentators have acknowledged the importance of “within-country diversity,” but to date this issue has received minimal attention. Our findings, based on a sample of 59,092 foreign acquisitions across 67 acquirer and 69 target countries, indicate that the diversity of languages and religions within the target’s home country may be an additional source of internal uncertainty and information asymmetry, above and beyond the uncertainty and asymmetry attributable to the linguistic and religious distances between the acquirer and target countries. In contrast, the diversity of languages and religions within the acquirer’s home country act as a source of tacit knowledge, moderating the firm's response to the distance and diversity of the target’s home country. The results indicate that firms from more diverse countries are more aware of the difficulties associated with diverse and distant countries, and in response, more strongly seek out remedies, such as lower equity shareholdings.